Gold nanoparticle sensor for the visual detection of pork adulteration in meatball formulation - Md Eaqub, Ali; Uda, Hashim, Prof. Dr.; Shuhaimi, Mustafa, Assoc. Prof. Dr.; Yaakob, Che Man, Prof. Datuk Dr.; Kh. N. Islam (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/